Rozwiąż równanie:
a) x²+√3x-1=0
b)x(x-3)=(x+2)²
c)2x-(√3x-1)(√3x+1)=2x²+(x+2²)
d)2,3x+(√3x-1)(√3x+1)=2x²+(x+2²)
e)x(x-³/₅)=(x+2)²
f)x(x-3)+²/₆x=(x+2)²


Uprość wyrażenie:
a)3,44xy+2x-7,2xy-3,1x+2,1xy
b)5x(2x-3y)-(3x-3y)²
c)(2x-3)²-(x-1)(x+1)-2xy+3
d)²/√₂+2√2
e)⁷/√₂₊₃+1
prosze rozwiazac mi wszystko a nie tylko po jednym przykładzie:)

2

Odpowiedzi

2010-01-06T10:28:00+01:00
A) x²+√3x-1=0
Δ=3+4=7
√Δ=√7
x=[-√3-√7]/2 i
x=[-√3+√7]/2
b)x(x-3)=(x+2)²
x²-3x=x²+4x+4
-3x-4x=4
-7x=4/:(-7)
x=-4/7
c)2x-(√3x-1)(√3x+1)=2x²+(x+2)²
2x-(3x²-1)=2x²+x²+4x+4
2x-3x²+1=3x²+4x+4
-6x²-6x-3=0/:(-3)
2x²+2x+1=0
Δ=4-8<0
brak rozwiązań

d)2,3x+(√3x-1)(√3x+1)=2x²+(x+2²)-czy to jest dobrze napisane ?
2,3x+3x²-1=2x²+x+4
x²+1,3x-5=0
Δ=1,69+20

1 1 1
2010-01-06T11:14:47+01:00
Rozwiąż równanie:
a) x²+√3x-1=0
Δ=3+4=7
√Δ=√7
x₁=[-√3-√7]/2
x₂=[-√3+√7]/2

b)x(x-3)=(x+2)²
x²-3x=x²+4x+4
x²-x²-3x-4x=4
-7x=4/:(-7)
x=-4/7

c)
2x-(√3x-1)(√3x+1)=2x²+(x+2)²
2x-(3x²-1)=2x²+x²+4x+4
2x-3x²+1=3x²+4x+4
-3x²-3x²+2x-4x+1-4=0
-6x²-2x-3=0
Δ=4-4*(-6)*(-3)=4-72=-68<0
brak rozwiązań

d)
2,3x+(√3x-1)(√3x+1)=2x²+(x+2)²
2,3x+3x²-1=2x²+x²+4x+4
3x²-3x²+2,3x-4x=4+1
-1,7x=5 /:(-1,7)
x=-5:1 ⁷/₁₀
x=-5: ¹⁷/₁₀
x=-5× ¹⁰/₁₇
x=-⁵⁰/₁₇

e)
x(x-³/₅)=(x+2)²
x²-³/₅x=x²+4x+4
x²-x²-³/₅x-4x=4
-4 ³/₅x=4
-²³/₅x=4 /:(-²³/₅)=
x=4×(-⁵/₂₃)
x=-²⁰/₂₃

f)
x(x-3)+²/₆x=(x+2)²
x²-3x+⅓x=x²+4x+4
x²-x²-2⅔x-4x=4
-6⅔x=4
-²⁰/₃x=4 /:(-²⁰/₃)
x=4×(-³/₂₀)
x=-³/₅

Uprość wyrażenie:
a)3,44xy+2x-7,2xy-3,1x+2,1xy=
=-1,66xy-1,1x

b)5x(2x-3y)-(3x-3y)²=
=10x²-15xy-9x²+18xy-9y²=x²+3xy-9y²

c)(2x-3)²-(x-1)(x+1)-2xy+3=
4x²-12x+9-x²+1-2xy+3=3x²-12x-2xy+13

d)²/√₂+2√2=²/√₂ ×√²/√₂ +2√2=²√²/₂ +2√2=√2+2√2=3√2

e)⁷/(√₂₊₃)+1=⁷/(√₂₊₃) ×(√²⁻³)/(√₂₋₃) +1=⁷(√²⁻³)/(₂₊₉) +1=
(7√2 -21)/11 +11/11=(7√2 -10)/11





2 4 2